Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-1018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Glottal Closure Instants in Degraded Speech Using Single Frequency Filtering Analysis

Abstract: Impulse-like characteristics of excitation occur at the glottal closure instant (GCI) due to sharp closure of the vibrating vocal folds in each glottal cycle. The GCIs are detected from the excitation component of the speech signal, and the excitation component is derived using inverse filtering or its variants. In this paper we propose a method for GCI detection based on single frequency filtering (SFF) of the speech signal. The SFF output has high signal-to-noise ratio (SNR) property in speech regions. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In addition, we conclude that the proposed Mel-SFF spectrogram system distinguishes dialects better from short utterances than its STFT-based reference system. In the future, we plan to explore the Mel-SFF spectrogram derived features for dialect identification in noisy conditions [27], [28], [30] and for larger corpora. Further, we plan to investigate the complementary information between the SFF based spectrograms and zero-time windowing (ZTW) based spectrograms, which were shown to give better performance over STFT [42]- [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we conclude that the proposed Mel-SFF spectrogram system distinguishes dialects better from short utterances than its STFT-based reference system. In the future, we plan to explore the Mel-SFF spectrogram derived features for dialect identification in noisy conditions [27], [28], [30] and for larger corpora. Further, we plan to investigate the complementary information between the SFF based spectrograms and zero-time windowing (ZTW) based spectrograms, which were shown to give better performance over STFT [42]- [44].…”
Section: Discussionmentioning
confidence: 99%
“…The SFF method is used to derive the amplitude envelope of the speech signal at every sample for a given frequency [32]. The SFF spectrum has been shown to be useful in finding burst-onset points [29] and glottal closure instants [30], and it has been demonstrated to exhibit high spectral resolution for important speech features such as harmonics and resonances [27].…”
Section: A Sffmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects due to waveform distortion are reduced in the SFF outputs, as we consider the envelope of the signal at each frequency separately. Although filtering causes smearing of the signal in the time domain due to closeness of the root to the unit circle in the z-plane, the impulse sequence characteristics are preserved in the SFF output at each frequency [2,9]. Thus, the crosscorrelation of the SFF envelopes is not affected by the waveform distortion.…”
Section: Time Delay Estimation (Tde)mentioning
confidence: 99%
“…From the studies in [18], it was observed that most of the epoch detection methods were shown to provide good accuracy on the speech data collected in the lab environments. Also, some attempts were made to see the effectiveness of these methods for additive noise degraded conditions [19][20][21][22][23]. However, there are not many attempts in GCI detection for the degraded conditions like telephone quality speech.…”
Section: Introductionmentioning
confidence: 99%